2011
DOI: 10.1177/1053815111427445
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between the Responsiveness of Fathers and Mothers and the Object Play Skills of Children With Autism Spectrum Disorders

Abstract: In this observational study, the concurrent relationships between the verbal and play responsiveness of 16 mothers and fathers and the object play skills of 16 children with Autism Spectrum Disorders (ASD) were investigated. First, the frequencies of children's play at four levels (i.e., exploratory, relational, functional, and symbolic) across unsupported, motherchild, and father-child play conditions were compared. Next, relationships between mothers' and fathers' verbal responsiveness and the object play sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 26 publications
4
36
1
3
Order By: Relevance
“…Moreover, we found a strong positive correlation between maternal verbal solicitation of symbolic play and children actual symbolic play for mothers of children with ASD only. This result suggests that, like all mothers, mothers of children with ASD play a crucial role in their psychological development, but they might contribute even more to determine their actual achievements reducing the effect of the potential limitations imposed by their pervasive deficits (Flippin and Watson, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found a strong positive correlation between maternal verbal solicitation of symbolic play and children actual symbolic play for mothers of children with ASD only. This result suggests that, like all mothers, mothers of children with ASD play a crucial role in their psychological development, but they might contribute even more to determine their actual achievements reducing the effect of the potential limitations imposed by their pervasive deficits (Flippin and Watson, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Within the autism spectrum disorder (ASD) literature, it has been reported by Flippin and Watson (2011) that children with ASD are likely to engage in more relational play with mothers than with fathers. Their study showed that, although both mothers and fathers used similar proportions of responsive play behavior and use of both parents' verbal and play behaviors correlated significantly with higher-level child object play, the use of responsive play behavior was correlated with higherlevel object play only for fathers.…”
Section: Discussionmentioning
confidence: 99%
“…A literatura na área da IP considera e apresenta numerosos estudos onde estão referenciados os diferentes benefícios que as famílias obtêm, pelo fato de serem apoiadas pela IP. A investigação tem documentado, de forma consistente, que a IP tem demonstrado e concretizado resultados positivos para as famílias no que concerne ao bem-estar e qualidade de vida, ao desenvolvimento de competências e controle sobre as suas vidas, à melhoria do conhecimento e da informação obtida e ao nível da promoção da participação/envolvimento das famílias em todo o processo de apoio (DEC, 2014;DEMPSEY;KENN, 2008;BRUDER;ESPE-SHERWINDT, 2014;FLI-PPIN;WATSON, 2011;LEITE;PEREIRA, 2013;MANZ, et al, 2014).…”
Section: Conclusõesunclassified